(untitled) (CIPEEX, 2025)
Facial anamnesis plays a crucial role in aesthetic practice, allowing the esthetician to deeply understand the state of the skin and the individual needs of each client. With the evolution of techniques and the increase in the sophistication of aesthetic treatments, the relevance of a detailed anamnesis has become even more evident. The facial clinical anamnesis was designed to better understand the patient’s daily life. During this process, questions are asked about the use of products, allergic history, medication, history of diseases and surgeries, eating habits, use of contact lenses, sleep quality, among other aspects. This review aims to evaluate current advances and practices in the performance of facial anamnesis by estheticians, examining how new approaches, technologies, and methodologies have impacted the effectiveness of aesthetic diagnoses and treatments. The review was conducted through a search in academic databases such as PubMed, Scopus, and Google Scholar, using keywords such as facial anamnesis, aesthetics, facial diagnosis, and skin assessment. Articles published in the last five years that addressed techniques, methodologies, and innovations in facial anamnesis were selected. The analysis included case studies, reviews, and experimental research. The results reveal that the practice of facial anamnesis has evolved significantly. A more comprehensive approach is observed, which considers not only the characteristics of the skin but also the health history and habits of the client, essential aspects for an accurate diagnosis. The importance of effective communication was highlighted, suggesting that an open and well-structured dialogue with the client is key to obtaining accurate and relevant information. The integration of evidence-based practices in facial anamnesis improves the standardization of procedures and treatment outcomes. Facial anamnesis has benefited from significant technological and methodological advances in the last five years. The combination of holistic approaches, advanced technologies, and improved communication skills has the potential to transform the practice of facial anamnesis, providing more accurate diagnoses and more effective treatments. The adoption of these innovations allows estheticians to offer personalized and high-quality care, thus improving aesthetic results and customer satisfaction. The continuous evolution of practice underlines the importance of constant updating and adaptation to new discoveries and available tools.